Exploring the Experiences and Perceptions of Individuals who have Completed the Discovery Health Family History Tool, and how the Personalised Report has Impacted their Lives - Barlow, Robyn Amy (Division of Human Genetics, 2021)
Since the completion of the Human Genome Project in 2003, the focus of genomic medicine has expanded to include the more common chronic diseases which are now understood to be multifactorial in origin. These diseases show strong familial clustering, as family members share both genetic and non-genetic risk factors, and therefore a positive family history is considered a risk factor for these diseases. Although a 3-generation pedigree is considered the gold standard for the collection of family health history (FHH) information and the stratification of disease risk, it is underutilised in health care due to various practitioner and patient barriers. Electronic patient-facing tools have been designed to interrogate FHH, with the capability of stratifying disease risks and making management and intervention recommendations, as an effective way of overcoming some of these barriers. Through the identification of at-risk individuals and targeted interventions, the hope is individuals will be more compliant and these programmes will be more effective than standardised health messages. Discovery Health introduced a FHH tool in April 2017, called MyFamilyHistory, to promote disease prevention and future wellness in its members. The tool estimates and reports on an individual's FHH-related lifetime risk for seven chronic diseases and makes recommendations to manage those risks. There is some evidence that FHH tools and personalised risk stratifications do result in screening uptake but only a few studies have looked at the effectiveness of FHH tools at achieving behaviour change and promoting a healthy lifestyle. Additionally, there are limited studies that have looked at the perceptions of the patients who have completed these FHH tools. This study therefore aimed to explore the experiences and perceptions of individuals who have completed Discovery Health's MyFamilyHistory tool, and how the personalised report has impacted their lives. This qualitative study drew on the principles of phenomenology and twelve participants were recruited through purposive sampling. They were recruited from the pool of individuals who had completed the MyFamilyHistory tool in 2019 and were recruited once they had contacted the researcher in response to a participation invitation sent out by Discovery Health. The data was collected through semi-structured, video interviews and thematic analysis was used to analyse the data. Five themes were identified from the data, namely: 1) Patient-Facing Tool, 2) Health Awareness, 3) Trust, 4) Hope for the Future, and 5) Achieving Change. It was found that the MyFamilyHistory tool is user-friendly and relatively easy-to-use and that the risks and recommendations were presented in a way that was easy to understand. The tool provided an improved health awareness and drew attention to risk factors including FHH. Benefits highlighted included it being a tool that promoted both health education and health communication, however the biggest challenge experienced was the lack of post-completion support and follow-up. Behaviour change was linked to the individuals perceived risk, rather than the risk generated by the tool, which is affected by various personal and environmental factors and furthermore was greatly influenced by the individual's health literacy level. Therefore, varying degrees of behaviour change were noted. This study highlights the important role that FHH tools have in health awareness and education as well as the importance of health literacy in achieving a healthier population. It also provides support for the role of health literacy in risk perception and how a less than optimum health literacy not only limits health awareness but also prevents proactive measures from being taken and impedes the health decision-making process. The findings of this study are likely to inform the implementation of personalised, preventative medicine and its role as an alternative and/or a complementary method to achieving health behaviour change. Additionally, the results can be used by Discovery Health, not only to improve their own tool but also to improve the service they offer to their members and the effectiveness thereof.